In PSC with dominant bile duct stenosis, IBD is associated with an increase of carcinomas and reduced survival - Rudolph, Gerda; Gotthardt, Daniel; Klöters-Plachky, Petra; Rost, Daniel; Kulaksiz, Hasan; Stiehl, Adolf (Journal of hepatology, 2010)
Background & Aims - In patients with primary sclerosing cholangitis (PSC) treated with ursodeoxycholic acid (UDCA), dominant stenoses are associated with reduced survival free of liver transplantation and the role of inflammatory bowel disease (IBD) in such patients is unclear. In the present study the influence of IBD on the outcome in patients with and without dominant stenosis has been evaluated. - Methods - In a prospective study, 171 patients were followed for up to 20years. All patients were treated with ursodeoxycholic acid; patients with dominant stenosis in addition were treated endoscopically. - Results - A total of 97 out of 171 patients had or developed dominant bile duct stenoses and 96 out of 97 were treated endoscopically. In patients with dominant stenosis without IBD, no carcinoma was found whereas all six bile duct and two gallbladder carcinomas and 6/7 colo-rectal carcinomas were found in patients with dominant stenosis with IBD (p=0.012). In patients without dominant stenosis but with IBD, 1 out of 7 had colo-rectal carcinoma. In patients with dominant stenosis without IBD (n=30), actuarial survival free of liver transplantation at 18years was 77.8% and in those with dominant stenosis and inflammatory bowel disease (n=67) it was 23.0% (p=0.045). In PSC patients without dominant stenosis and without IBD (n=21), actuarial survival free of liver transplantation at 18years was 68.2% and in those with inflammatory bowel disease (n=53) it was 78.4% (n.s.). - Conclusions - In patients without dominant stenosis, IBD had no effect on the incidence of carcinomas and survival. Only patients with dominant stenosis with additional IBD had an increased carcinoma rate. This may contribute to the reduced survival free of liver transplantation in such patients.